IMPLEMENTASI ACTIVE LEARNING BERBASIS VIDEO ANIMASI INFOGRAFIS PADA PELAJARAN BAHASA INDONESIA DI MI AL URWATUL WUTSQO 1 - Laily, Hikmatul; Mahsun, Ali (Al-Adawat : Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2024)
Indonesia language learning at the madrasah ibtidaiyah level requires innoative methods and media to make it easier for students to understand the material and develop their language skills. On of the methods and media that can be used is active learning based on animated infograpic videos. This research aims to analyze the implementation of active learning using animared infographic videos in Indonesian language learning at MI Al Urwatul Wutsqo 1. The research method is descriptive qualitative with 6th grade students as the research subjects. The animated infograohic video based learning media is applied to improve students understanding of the subject matter. The research result show that the use of animated infographic videos in the active learning model can enchance students learning outcomes and increase their undestanding of indonesia languasge learning. It also provides motivation, enthusiasm, and fosters discussion. Additionally, students show a higher level of interest and oarticipation in Indonesia language learning. Based on these results, it can concluded that this media is recommended for use in Indonesian langauge learning at schools.